A rare case of MGRS with immunotactoid glomerulopathy responding to bortezomib, dexamethasone, and rituximab. Issue 10 (22nd June 2020) - Kuang, Chaoyuan; Quann, Kevin; Liman, Agnes K.; Frye, Roy; Alshoubaki, Nawras; Ramkumar, Mohan; Liman, Andrew D.
Abstract: Patients with monoclonal gammopathy of renal significance should be treated with clone‐directed therapy against sources of monoclonal proteins in order to prevent progression to more advanced monoclonal gammopathies and renal failure. Abstract : Patients with monoclonal gammopathy of renal significance should be treated with clone‐directed therapy against sources of monoclonal proteins in order to prevent progression to more advanced monoclonal gammopathies and renal failure.